SARS–CoV‐2 Infection and COVID‐19 Outcomes in Rheumatic Diseases: A Systematic Literature Review and Meta‐Analysis. Issue 5 (28th March 2022) - Conway, Richard; Grimshaw, Alyssa A.; Konig, Maximilian F.; Putman, Michael; Duarte‐García, Alí; Tseng, Leslie Yingzhijie; Cabrera, Diego M.; Chock, Yu Pei Eugenia; Degirmenci, Huseyin Berk; Duff, Eimear; Egeli, Bugra Han; Graef, Elizabeth R.; et al.
Abstract : Objective: The relative risk of SARS–CoV‐2 infection and COVID‐19 disease severity among people with rheumatic and musculoskeletal diseases (RMDs) compared to those without RMDs is unclear. This study was undertaken to quantify the risk of SARS–CoV‐2 infection in those with RMDs and describe clinical outcomes of COVID‐19 in these patients. Methods: We conducted a systematic literature review using 14 databases from January 1, 2019 to February 13, 2021. We included observational studies and experimental trials in RMD patients that described comparative rates of SARS–CoV‐2 infection, hospitalization, oxygen supplementation/intensive care unit (ICU) admission/mechanical ventilation, or death attributed to COVID‐19. Methodologic quality was evaluated using the Joanna Briggs Institute critical appraisal tools or the Newcastle‐Ottawa scale. Risk ratios (RRs) and odds ratios (ORs) with 95% confidence intervals (95% CIs) were calculated, as applicable for each outcome, using the Mantel‐Haenszel formula with random effects models. Results: Of the 5, 799 abstracts screened, 100 studies met the criteria for inclusion in the systematic review, and 54 of 100 had a low risk of bias. Among the studies included in the meta‐analyses, we identified an increased prevalence of SARS–CoV‐2 infection in patients with an RMD (RR 1.53 [95% CI 1.16–2.01]) compared to the general population. The odds of hospitalization, ICU admission, and mechanical ventilation were similar in patients with and those without an RMD, whereas the mortality rate was increased in patients with RMDs (OR 1.74 [95% CI 1.08–2.80]). In a smaller number of studies, the adjusted risk of outcomes related to COVID‐19 was assessed, and the results varied; some studies demonstrated an increased risk while other studies showed no difference in risk in patients with an RMD compared to those without an RMD. Conclusion: Patients with RMDs have higher rates of SARS–CoV‐2 infection and an increased mortality rate.